Geniposide Causes Idiopathic Mesenteric Phlebosclerosis - Chuah, Yoen Young; Lee, Yeong Yeh (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Young Chuah Y, Yeh Lee Y. Geniposide causes idiopathic mesenteric phlebosclerosis. Turk J Gastroenterol. 2023;34(8):890-891.